Colon specific CODES based Piroxicam tablet for colon targeting: statistical optimization, in vivo roentgenography and stability assessment. (25th November 2013) - Singh, Amit Kumar; Pathak, Kamla
Abstract: This study was aimed to statistically optimize CODES™ based Piroxicam (PXM) tablet for colon targeting. A 3 2 full factorial design was used for preparation of core tablet that was subsequently coated to get CODES™ based tablet. The experimental design of core tablets comprised of two independent variables: amount of lactulose and PEG 6000, each at three different levels and the dependent variable was %CDR at 12 h. The core tablets were evaluated for pharmacopoeial and non-pharmacopoeial test and coated with optimized levels of Eudragit E100 followed by HPMC K15 and finally with Eudragit S100. The in vitro drug release study of F1–F9 was carried out by change over media method (0.1 N HCl buffer, pH 1.2, phosphate buffer, pH 7.4 and phosphate buffer, pH 6.8 with enzyme β-galactosidase 120 IU) to select optimized formulation F9 that was subjected to in vivo roentgenography. Roentgenography study corroborated the in vitro performance, thus providing the proof of concept. The experimental design was validated by extra check point formulation and Diffuse Reflectance Spectroscopy revealed absence of any interaction between drug and formulation excipients. The shelf life of F9 was deduced as 12 months. Conclusively, colon targeted CODES™ technology based PXM tablets were successfully optimized and its potential of colon targeting was validated by roentgenography.